2019
DOI: 10.1097/md.0000000000016403
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl-based intravenous patient-controlled analgesia with low dose of ketamine is not inferior to thoracic epidural analgesia for acute post-thoracotomy pain following video-assisted thoracic surgery

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Tseng et al (16) emphasized the results of our study as they examined a combination of fentanyl and low-dose ketamine as patient-controlled analgesia (PCA) versus epidural PCA in 70 patients after video-assisted thoracic surgery.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Tseng et al (16) emphasized the results of our study as they examined a combination of fentanyl and low-dose ketamine as patient-controlled analgesia (PCA) versus epidural PCA in 70 patients after video-assisted thoracic surgery.…”
Section: Discussionmentioning
confidence: 92%
“…Ketamine has been tested in many studies to examine its analgesic effect either preoperatively or intraoperatively (9)(10)(11)(12)(13)(14)(15)(16)(17). Minoshima et al (14) examined a low dose of ketamine infusion 48 h intra-and postoperatively versus the placebo in 36 patients subjected to scoliosis corrective surgery and found that Ketamine infusion reduced morphine consumption significantly over the next 48 h.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of epidural has been validated in previously published smaller series. [ 6 , 7 , 13 , 14 ] Further studies addressing newer analgesic techniques like paravertebral blocks, serratus anterior block, and erector spinal plane block would be needed to scientifically address optimal pain control in patients undergoing lung transplantation via T.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, opioid-based IV-PCA with an adjunct could provide sufficient pain relief, similar to thoracic epidural analgesia, after video-assisted thoracic surgery, leading to moderate-to-severe postoperative pain. 11 Hausken et al 17 20 demonstrated that intraoperative DEX infusion could decrease bleeding and provide a better surgical field, because of more stable hemodynamics. In addition, a meta-analysis showed that systemic administration of DEX could significantly decrease intraoperative blood loss in nasal surgery.…”
Section: Discussionmentioning
confidence: 99%